Correction: Direct growth of a porous substrate on high-quality graphene via in situ phase inversion of a polymeric solution. Issue 45 (12th November 2020) - Qin, Yanzhe; Koehler, Stephan; Hu, Yongyou; Wu, Yuqing; Peng, Xinwen; Ni, Ming
Abstract : Correction for 'Direct growth of a porous substrate on high-quality graphene via in situ phase inversion of a polymeric solution' by Yanzhe Qin et al., Nanoscale, 2020, 12, 4953–4958, DOI: ; 10.1039/C9NR09693K .